2014
DOI: 10.1111/jth.12635
|View full text |Cite
|
Sign up to set email alerts
|

A novel F8 −/− rat as a translational model of human hemophilia A

Abstract: and had a significantly prolonged activated partial thromboplastin time (APTT) and clot formation time as compared with wild-type (WT)/WT rats. In vitro spiking of rat plasma with human recombinant FVIII resulted in dosedependent normalization of the APTT. Conclusion: On the basis of the targeted deletion in F8, and the distinct physical and analytic characteristics of the rat, we conclude that an FVIII-deficient rat strain has been generated that has the potential to contribute greatly to translational resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…This facilitates the use of the animals as their own controls during longitudinal disease progression studies, thereby refining study design and probably reducing the required number of animals. Finally, the F8 −/− rats develop spontaneous bleeds comparable to human hemophilia patients , indicating a high translational potential of this animal model (although in the current study 10% experienced large spontaneous bleeds, causing exclusion of these animals).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…This facilitates the use of the animals as their own controls during longitudinal disease progression studies, thereby refining study design and probably reducing the required number of animals. Finally, the F8 −/− rats develop spontaneous bleeds comparable to human hemophilia patients , indicating a high translational potential of this animal model (although in the current study 10% experienced large spontaneous bleeds, causing exclusion of these animals).…”
Section: Introductionmentioning
confidence: 63%
“…; Pfizer, Paris, France) or vehicle buffer solution (10 m m L‐Histidine, 8.8 m m sucrose, 30.8 m m NaCl, 1.7 m m CaCl 2, 0.01% Tween 80) at a volume equivalent to rhFVIII‐dosed animals. The rhFVIII dose was based on complete in vitro normalization of APTT in F8 −/− rat plasma , as well as experience in handling spontaneous bleeds in the F8 −/− rat population (unpublished data). WT rats received buffer solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a F8 −/− rat model for haemophilia A was developed, which is phenotypically comparable to human patients, with impaired haemostasis and suffering from spontaneous musculoskeletal bleeding . We have previously reported that after a single induced joint bleed, F8 −/− rats develop histopathological changes in the knee resembling human HA, attenuable by recombinant human FVIII (rhFVIII) treatment .…”
Section: Introductionmentioning
confidence: 99%
“…It has been yet used in some transfusion protocol and in cardiac and liver surgery [25,26] and recent studies try to increase its application scope [27]. In rats, TEM is increasingly used to measure coagulability in research [28,29]. Thus, it might help to refine ED50 test in rats by replacing INR.…”
Section: Assessmentmentioning
confidence: 99%